Perception of the control ability principle and its consequences for budgetary control / Ryota Machida and Tomoki Oshika - Machida, Ryota; Oshika, Tomoki (Universiti Teknologi MARA, 2021)
In this study, we empirically examined the following three relationships through quantitative analysis of web-based survey data collected from managers of Japanese firms. First, we examined the relationship between managers' perceptions of controllability and budget use. Second, we examined the relationship between budget use and altruistic behavior. Third, based on managers' perceptions of controllability, we examined the relationship between altruistic behavior and managerial performance. Structural equation modeling revealed that not only did perception of low controllability by managers promoted the use of budgeting, it also promoted organizational citizenship behavior through increased trust in superiors, which subsequently enhanced managerial performance.